Integrating Moderate Religious Values into School Curricula and Management Through an Ethnographic Approach - Zainal Abidin; Ahmad Qusairi; Muhamad Maulana (AT-TA'LIM, 2026)
Religious polarization in Indonesia demands that educational institutions play a strategic role in instilling religious moderation, yet many schools face challenges in effectively integrating these values in a heterogeneous environment. This study aims to analyze the mechanisms of integration of religious moderation values into the curriculum and management at SMK Negeri Sukapura, a public school that has successfully fostered harmony between Muslim and Hindu students. Using a qualitative ethnographic approach through participant observation, in-depth interviews with the principal, teachers, and students, and analysis of curriculum documents and school policies, this study explores the concrete practices and hidden curriculum that shape a culture of tolerance. The results identify three key mechanisms: (1) transformational leadership that shapes social norms through role models and participatory policies, (2) integration of moderation values across subjects through a dialogic and reflective approach, and (3) a hidden curriculum that changes attitudes through spontaneous interactions, inclusive extracurricular activities, and symbolic justice in worship facilities. The school's success lies in the systemic synergy between leadership, managerial policies, formal curriculum, and mutually reinforcing school culture. This study provides a theoretical contribution by conceptualizing moderation as an ecological system, not an isolated intervention, and offers an applicable empirical model for heterogeneous public schools in implementing religious moderation-based character education in Indonesia.